Delivering the UK Energy Transition with an Accountable and Competitive Electricity Sector: Theory and Realities - Lucie de Carvalho (Revue Française de Civilisation Britannique)
This article discusses accountability in UK electricity services against the backdrop of the energy transition. Today’s decarbonisation imperatives stand as a major accountability test for the UK government and the electricity regulator, which have been grappling with the energy trilemma since the early 2000s. The analysis will determine the extent to which both have responded to these new goals while still abiding by their original mandate to uphold the public interest. Climate change imperatives have actually brought to the surface enduring faulty accountability dynamics, which had at first been obscured – by practice or design – by the new public management reforms of the early 1990s. The inherently ad hoc and flexible British accountability culture therefore appears to have contributed to hampering the country’s progress towards decarbonisation.